GREEK MYTHOLOGY AS SEEN IN RICK RIORDAN’S THE LIGHTNING THIEF - Muhamad Nurul Hikmat (Universitas Gadjah Mada, 2012)
The novel by Rick Riordan entitled The Lightning Thief is written based on Greek Mythology. This mythology is The Greek’s manifestation of culture that ages thousands years. To reveal the representation of Greek Mythology in The Lightning Thief as a cultural manifestation, study and analysis is conducted through dynamic structuralism approach focusing on plot, characters and settings (factual structure) of the novel. The plot is originated from three Greek heroes’ stories. The characters involve four significant mythological characters out of twenty seven mythological characters in the novel including four demigods, five gods, one Titan and seventeen mythological creatures. While in the setting of place, there are two places related to Greek mythology.